Graduate Students May Need Information Literacy Instruction as Much as Undergraduates - Miller, Robin Elizabeth (Evidence Based Library and Information Practice, 2014)
A Review of: Conway, Kate. (2011). How prepared are students for postgraduate study? A comparison of the information literacy skills of commencing undergraduate and postgraduate studies students at Curtin University. Australian Academic & Research Libraries, 42(2), 121-135. Abstract Objective – To determine whether there is a difference in the information literacy skills of postgraduate and undergraduate students beginning an information studies program, and to examine the influence of demographic characteristics on information literacy skills. Design – Online, multiple choice questionnaire to test basic information literacy skills. Setting – Information studies program at a large university in Western Australia. Subjects – 64 information studies students who responded to an email invitation to participate in an online questionnaire, a 44% response rate. Of those responding, 23 were undergraduates and 41 were postgraduates. Methods – Over the course of two semesters, an online survey was administered. In order to measure student performance against established standards, 25 test questions were aligned with the Australian and New Zealand Information Literacy Framework (ANZIIL) (Bundy, 2004), an adapted version of the ACRL Information Literacy Standards for Higher Education (Association of College & Research Libraries, 2000). In the first semester that the survey was administered, 9 demographic questions were asked and 11 in the second semester. Participants were invited to respond voluntarily to the questionnaire via email. Results were presented as descriptive statistics, comparing undergraduate and postgraduate student performance. The results were not tested for statistical significance and the author did not control for confounding variables. Main Results – Postgraduate respondents scored an average of 77% on the test questionnaire, while undergraduates scored an average of 69%. The 25% of respondents who had previous work experience in a library achieved average scores of 79%, in contrast to 69% among those who had not worked in a library. Average scores for undergraduates in the 20-30 age group were 81%, while those in the 30-40 age group averaged 65%. Among both undergraduate and postgraduate students, scores may indicate deficiencies in information literacy skills in several areas, including parsing citations, strategies for locating specific content, and defining an information need. Conclusion – The study concludes that postgraduate students’ information literacy skills may be marginally better than the skills of undergraduates. Age was found to be associated with higher performance among undergraduate students, and a variety of “basic” information literacy skills may elude many respondents. These findings might prompt librarians and instructors to look closely at gaps in information literacy knowledge among students at both the undergraduate and postgraduate level.